Content Validity of Job Characteristic Model for Graduates with Learning Disabilities in the Food Service Industry - Nik Othman, Nik Norlaili Jamilah; Kamaruzaman, Fathiyah Mohd; Rasul, Mohamad Sattar; Suradin, Salwa; Ab Hamid, Norzaharah (Journal of Technical Education and Training, 2025)
Graduates with learning disabilities (LD) face distinct challenges and opportunities, especially in food service. The Job Characteristics Model (JCM) is used to assess LD graduates’ work characteristics’ content validity. Quantitative study was conducted with food service employers and vocational educators. JCM dimensions’ compatibility with LD graduates’ practical abilities and employment ability is the main goal. Experts were selected using purposive sampling. Six professionals verified content validation instruments for the study. An item-level content validity index (I-CVI) was utilised to determine expert’s consensus qualities with the JCM construct. There were five JCM constructs suitable for (LD) grads and validated them with 1.00 I-CVI by a panel of experts. Accepted instruments with excellent content validity surpass > 0.80 take-off value. Two items were removed and 27 items fitted to the food service job profile and work scope. Acceptable and meaningful instrument findings were found. It provides a novel and relevant indication of (LD) graduates’ workforce readiness. The data also show that JCM is a valuable paradigm, although some features need changes to properly assist LD graduates. To improve employment outcomes, the study recommends personalised job designs and support structures, such as increased training programmes and adjusted job responsibilities. These findings can help policymakers, vocational training programmes, and food service industry create more inclusive and supportive workplaces for people with learning disabilities